Literasi Keuangan Untuk Pengembangan Bumdes Dengan Pendekatan Teknologi Informasi Dan Komunikasi - Irawan, Dudi; Wijaya, Guruh; Wardoyo, Ari Eko (Journal Of Humanities Community Empowerment, 2023)
OJK defines financial literacy as knowledge, skills and beliefs that influence attitudes and behavior to improve the quality of decision-making and financial management in order to achieve prosperity. The percentage of financial literacy in Indonesia is still considered quite low, only 38.03%. Village Owned Enterprises BUMDES are business entities whose capital is wholly or partly derived from the village, and the existence of BUMDES is intended to create jobs or improve public services for the better community. The existence of BUMDES is very important for villages and villagers because in concept it is an institution that supports the village economy, so seriousness is needed in managing and running BUMDES so that everything planned can run smoothly and successfully. One indicator of the success of BUMDES is that the administrators who are included in the management organizational structure understand financial literacy. Financial literacy can be seen as a preventive step to equip BUMDES administrators to avoid difficulties related to financial management problems. The results obtained after carrying out this community service activity are that the partners actually know and carry out activities related to financial transactions, but there is still much that needs correction in accordance with financial literacy, and after this community service activity the partners understand and understand more what it is and the importance of everything that includes financial activities, especially those related to BUMDES management